Saberes docentes mobilizados no ensino de matemática por atividades experimentais: articulações entre elementos da análise de modelos e tecnologias digitais na formação contínua de professores - SILVA, Francisco Robson Alves da (Universidade Federal do Oeste do Pará, 2024)
This study analyzes the teaching knowledge mobilized by Basic Education teachers when they integrate Model Analysis (AnM), Digital Information and Communication Technologies (TDIC) and Mathematics Teaching through Experimental Activities (EMAE) in their pedagogical practices. Based on the work of Tardif, Pimenta and Shulman on teaching knowledge, a qualitative methodology focused on continuous training is adopted. The project included the offering of a mini course, made up of four offices, which proposed innovative methodologies, encouraging participating teachers to reformulate their educational practices. The results indicate that teachers mobilized pedagogical, experiential, curricular and disciplinary knowledge effectively, adapting their practices to contemporary educational demands. Among the challenges, the limitations of technological infrastructure and institutional support stand out, partially overcome by the collaboration and engagement of participants. The strategies adopted promote dynamic and interactive learning environments, improving student understanding and engagement. It is proposed to create the Base of Educational Studies in Mathematics (BEEM), a theoretical-methodological structure that integrates teaching knowledge with innovative pedagogical practices, evolving into collaboration and teaching reflection. Thus, this study contributes significantly to the field of Mathematics Education, expanding the understanding of the mobilization of teaching knowledge and emphasizing the importance of investigative methodologies and the use of TDIC for the development of critical and innovative teaching practices.
Keywords: Formação contínua; Análise de modelos; Saberes docentes; Tecnologias Digitais; Ensino de Matemática; CNPQ:: CIÊNCIAS HUMANAS; Educação na Amazônia: formação do educador, práxis pedagógica e currículo